UJI FITOKIMIA DAN UJI TOKSISITAS EKSTRAK ETANOL BATANG BAJAKAH (Uncaria cordata (Lour.) Merr.) TERHADAP Artemia salina L. - Wardani, M. Rizky; Erwin, Erwin; Hairani, Rita (PROSIDING SEMINAR KIMIA, 2024)
Uncaria is a genus of plants that grows in the Kalimantan forest. Many species in this genus are used as traditional medicines, so this genus is interesting to be studied for its chemical compound content. One species in this genus is Uncaria cordata which is also known as Bajakah plant. The aim of this study was to determine the content of secondary metabolite compounds and the level of toxicity of the ethanol extract of U. cordata stems on Artemia salina L. The methods used in this research were extraction, phytochemical tests and toxicity test using the Brine Shrimp Lethality Test (BSLT) method. The results of the phytochemical test showed that the ethanol extract of U. cordata stems contained alkaloids, triterpenoids, phenolics, flavonoids, quinones, and saponins. Furthermore, according to of the toxicity test showed that the ethanol extract of U. cordata stems had toxicity level of 75.03 ppm in the toxic category (LC50 < 1000 ppm). Based on these results, it can be concluded that the ethanol extract of U. cordata stems has the potential to have bioactivity because it is toxic to Artemia salina L. shrimp larvae. Keywords: Bajakah, Phytochemicals, Secondary Metabolites, Toxicity, Uncaria cordata